A shortcut method for solving long-term thermal dynamic analysis of aircraft fuel tank by thermal node network analysis and OpenFOAM software. (November 2018) - Wang, Ri; Dong, Sujun; Meng, Fanchao; Guo, Dechun
This article addresses a long-term thermal dynamic analysis problem for aircraft fuel tank and the related solution. The new method combines the thermal node network analysis and the finite element numerical calculation based on the OpenFOAM software. Compared to the thermal node network analysis algorithm, the computational precision is significantly improved by numerical calculation on more delicate grid in the solid region. On the other hand, compared to conventional finite element numerical calculation method, the computational efficiency is significantly improved since the liquid level at every moment is determined by the volume integral of every grid along the gravity direction instead of volume of fluid method on the Fluent software and two thermal nodes are used to represent the air and the fuel, respectively, and solve the two-phase heat transfer with the fuel tank by the aid of grid computation of the heat exchange area. Taken a typical fuel tank heated by aerodynamic heat as an example, the results comparing to the volume of fluid calculation by Fluent software show that the computation time is reduced to 10.3%, while the max deviation of the tank wall temperature is kept within 6.5%, which meets the requirements of engineering calculation precision.